Menelaah Faktor-faktor yang Berdampak pada Kemampuan Berpikir Kritis Siswa Sekolah Dasar pada Pembelajaran Matematika - Rahmadani, Nadia; Nisa, Sahrun; Suriani, Ari (Lembaga Yasin AlSys, 2024)
The methodology used in qualitative research uses a qualitative approach and uses a qualitative narrative design. The results of the research show that the ability to think critically in mathematics for strata IV children at SDN 03 Sebungkang is very high, namely around 29.58 percent. The percentage of mathematics students who understand the topic well is around 63.33 percent. Additionally, they provide valid and relevant logarithmic penalties based on hypotheses or ideas, increasing the percentage to 26.67 percent. Lastly, increasing team collaboration between ideas to overcome mathematical problems from 13% and taking actions consisting of 15% of mathematics problems. around 13% and taking actions consisting of 15% of mathematics problems. 2) Psychological factors influence the ability to identify student criticism. The ability to identify student criticism. factors include their cognitive decline.